Advanced Glycation End Products (AGEs) Antibody Protects Against AGEs-induced Apoptosis and NF-Ä¸B p65 Subunit Overexpression in Rat Glomerular Culture - Adianingsih, Oktavia Rahayu; Lyrawati, Diana; Samsu, Nur (Journal of Tropical Life Science, 2016)
Advanced glycation end products (AGEs) have been thought to be a major cause of diabetic nephropathy (DN). The mechanisms underlying the involvement of AGEs antibody in diabetic nephropathy are not fully understood. The present study was designed to investigate the protective effect of AGEs antibody on AGEs-induced glomerular damage. Isolated glomeruli were pre-incubated either with 10 Âµg/mL polyclonal anti-AGEs antibody (AGE-pAb) or monoclonal anti-NÉœ -carboxymethyl-lysine antibody (CML-mAb) as a model of AGEs antibody to block interaction of AGEs with receptor for AGEs (RAGE) and incubated afterwards either with 100 Âµg/mL bovine serum albumin (BSA) or AGE-modified bovine serum albumin (AGE-BSA) for 48 h. Annexin V/nephrin doublestaining was performed to determine apoptosis. Using immunofluorescence, we found that administration of AGE-BSA not only significantly increased glomerular cells apoptosis and nuclear factor kappa B (NF-Ä¸B) p65 expression, but also reduced expression of nephrin, an important structural and signal molecule of podocytes slit diaphragm. Blocking the interaction of AGE-RAGE with AGEs antibody significantly protected glomerular cells from AGEs-induced apoptosis and NF-Ä¸B p65 overexpression. We found that AGE-pAb conferred superior protective effect compared with CmL-mAb for the same reduction in apoptosis and NF-Ä¸B p65 expression. In sharp contrast, CmL-mAb led to preserve expression of podocytes nephrin better than AGE-pAb. These results demonstrate that the antibody against AGEs may be beneficial for preventing the glomerular damage in DN.